Rheotaxis Based High-Throughput Motile Sperm Sorting Device - Hwang, Bohyun; Lee, Dongkyu; Hwang, Seung-Jun; Baek, Joong-Hwan; Kim, Byungkyu (International journal of precision engineering and manufacturing, 2019)
A progressive motile sperm sorting device with a diffuser-type microfluidic channel is proposed to improve fertilization in assisted reproductive technologies. When sperm cells swim against a fluid flow, they are positioned according to their motility in specific channel zones. A numerical simulation is carried out in a meso-sized diffuser-type channel which can realize high throughput to verify the working principle and the sorting device is fabricated based on the simulation result. Furthermore, to analyze the condition of the semen and investigate the experimental results, a novel image processing method is proposed. With the proposed analyzing technique, the sperm sorting experiment is performed in the channel using the canine semen sample. As a result, the %motility increases from 59.89 to 69.36%, however, it does not satisfy the reported guideline for canine sperm motility (%motility > 70%). Therefore, we perform a washing process by injecting DPBS fluids to improve indexes related to motility. After double washing procedures, we could increase %motility from 59.89 to 82.24%, motile sperm rate from 33.38 to 53.10% and motility index from 26.35 to 49.44 in Zone A, comparing to the prepared sample.